Intra-rater and inter-rater reliability of total faulty breathing scale using visual observation and videogrammetry methods. Issue 3 (July 2017) - Mohan, Vikram; Perri, Maria; Paungmali, Aatit; Sitilertpisan, Patraporn; Joseph, Leonard Henry; Jathin, Romizan; Mustafa, Munirah Bt; Mohd Nasir, Siti Hawa Bt
Abstract: Faulty breathing is an aspect of alteration in the normal fundamental pattern of breathing. The available existence of scales in assessing faulty breathing has not frequently been used. Measurement errors in assessing and quantifying breathing patterns may originate from unclear directions and variation between observers. This study determined the measure reliability of the Total Faulty Breathing Scale (TFBS) for quantifying breathing patterns. Twenty seven participants were recruited comprising healthy and unhealthy subjects. Two examiners assessed their breathing patterns using the TFBS on two different occasions with visual observation and a videogrammetry method. Evaluation of the observational breathing pattern method for intra-rater and inter-rater showed agreement of 96.30% and a kappa score of greater than 0.78, which indicated substantial agreements. The videogrammetry method showed a percent agreement of (100%) with a kappa score of (1.00). This study indicates that the TFBS is a considerably reliable tool for evaluating breathing patterns with both visual observation and a videogrammetry method.